2010
DOI: 10.1039/c0mb00002g
|View full text |Cite
|
Sign up to set email alerts
|

Stacking interaction in the middle and at the end of a DNA helix studied with non-natural nucleotides

Abstract: Base stacking is important for the base pair interaction of a DNA duplex, DNA replication by polymerases, and single-stranded nucleotide overhangs. To study the mechanisms responsible for DNA stacking interactions, we measured the thermal stability of DNA duplexes containing a non-natural nucleotide tethered to a simple aromatic hydrocarbon group devoid of dipole moments and hydrogen bonding sites. The duplexes containing tetrahydrofuran were paired with a deoxyadenosine derivative (A/T base pair analog) or a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…2 B includes the data of the DNA duplex containing the deoxycytidine derivative C naph that covalently tethers a stacking moiety of the naphthyl group as a simple structural analog of the DNA purine base. Our previous study revealed that the C naph /F pair allowed the intercalation of the naphthyl group into a DNA duplex without substantial perturbation of the overall double helical structure (28,29). Although the abasic site introduced in the sequence significantly decreased the duplex stability and the -Dn w , incorporation of C naph opposite the abasic site restored the values.…”
Section: Biophysical Journal 102(12) 2808-2817mentioning
confidence: 99%
“…2 B includes the data of the DNA duplex containing the deoxycytidine derivative C naph that covalently tethers a stacking moiety of the naphthyl group as a simple structural analog of the DNA purine base. Our previous study revealed that the C naph /F pair allowed the intercalation of the naphthyl group into a DNA duplex without substantial perturbation of the overall double helical structure (28,29). Although the abasic site introduced in the sequence significantly decreased the duplex stability and the -Dn w , incorporation of C naph opposite the abasic site restored the values.…”
Section: Biophysical Journal 102(12) 2808-2817mentioning
confidence: 99%
“…The fundamental interest in the molecular recognition at termini of DNA:RNA duplexes was one motivation for our current work that extends earlier work on DNA:DNA or RNA:RNA duplexes with modified dangling residues or caps. [45] In the optimization phase of our study, we chose peptidic linkers (Scheme 1b) both for their flexibility, synthetic ease, and the modest lipophilicity of the chain. Some long chain alkanes can stabilize DNA:DNA duplexes, [46] but strongly lipophilic caps or linkers can lead to hydrophobic dimerization, [47] and can complicate purification due to strong adsorption or micelle formation.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, a dangling A increases the duplex stability by 0.1~−1.0 kcal mol −1 , which is greater than that provided by a dangling C (0.3 ~−0.5 kcal mol −1 ), indicating the greater stacking strength of adenine than of cytosine. In contrast, we found that both A X and C X provided much more interaction energy (−0.1~−1.8 kcal mol −1 ) [44, 45], which was comparable to the formation of Watson-Crick A/T and C/G base pairs (–0.5~−1.8 kcal mol −1 ) and the stability reported for the dangling pyrene-modified nucleotide (−1.7 kcal mol −1 ) [19, 38]. The large stabilization energy suggests that the nonpolar aromatic groups efficiently stack with the terminal base pair by adopting the base pair-mimic geometry as indicated in Figure 5(a), in which the ureido linker may interact with N 1 of adenine or N 3 of cytosine.…”
Section: The Base Pair Analogs Of a Base Pair-mimic Structurementioning
confidence: 97%
“…It is a remarkable finding that, although the interaction mechanism differs between the base pair-mimic nucleoside and the Watson-Crick base pair, a linear free-energy correlation between them are exhibited: as the interaction free energy from the base pair analog increases, the interaction energy for the corresponding base pair formation (A X /F for A/T base pair, and C X /F for C/G base pair) increases [45]. A similar relationship was obtained with the dangling end data relative to the corresponding Watson-Crick base pairs (A X for A/T base pair and C X for C/G base pair).…”
Section: The Base Pair Analogs Of a Base Pair-mimic Structurementioning
confidence: 99%